Free Health Care Policy in Nepal: Recent Trend and Challenges - Gurung, G (Journal of Nepal Health Research Council, 2010)
The willingness to pay for services can not be equated with ability to pay for it. Despite of Alma-Ata declaration in 1978, developing countries have numerous challenges to meet the goal of health for all. In the quest for increasing access to health for all, Government of Nepal has recently introduced free health care policy. The efficacy of its implementation, operational challenges and issues related to the free health care, need to be reviewed. The unnecessary use of services, quality of care, risk of medicalization of public health services, mismanagement of drugs and health worker resistance towards the policy are some of its key challenges. To overcome these, community awareness and participation to monitor implementation of the policy is necessary and long term efficacy of this service has yet to be observed. Key words: community monitoring system; free health care policy; participation DOI: 10.3126/jnhrc.v7i2.3024 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 138-139